Problems with the taxonomy of Phytoptus tetratrichus Nalepa 1890 (Acari: Eriophyoidea) inhabiting Tilia spp.: Analysis based on morphological variation among individuals - Soika, Grażyna; Kozak, Marcin (Zootaxa, 2011)
The purpose of this research was to investigate both the qualitative and quantitative morphological traits of Phytoptus tetratrichus Nalepa 1890 populations inhabiting three different lime tree species: Tilia cordata Mill., Tilia tomentosa Moench and Tilia americana L.. Morphological characters of two populations collected from T. cordata and T. tomentosa over three successive growing seasons were compared with the aid of canonical variate analysis. Additionally, individuals occurring on T. americana in a consecutive year were also studied. Protogyne and deutogyne females were differentiated using both qualitative and quantitative traits. For deutogyne females, individuals from all combinations of Tilia species × year (which constituted populations for comparison) clearly differed from each other. However, the differences between populations from T. cordata and T. tomentosa were less distinct. For protogyne females, observed differences were clearly visible. The between-season variation in morphological characters such as body size appeared to be quite large, indicating that morphological analysis based on observations from only a single season can be inaccurate. Deutogyne females of P. tetratrichus were observed to cause various types of damage symptoms: leaf-roll galls along the leaf edges of T. cordata; small round erinea on the lower leaf surface and small wart-like galls on the upper leaf surface of T. tomentosa; fingerlike galls on both leaf surfaces of T. americana.